2017
DOI: 10.1007/s11270-017-3250-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Locating Leakages in Sewage Pressure Pipes Using the Distributed Temperature Sensing Technology

Abstract: The cost effective maintenance of underwater pressure pipes for sewage disposal in Austria requires the detection and localization of leakages. Extrusion of wastewater in lakes can heavily influence the water and bathing quality of surrounding waters. The Distributed Temperature Sensing (DTS) technology is a widely used technique for oil and gas pipeline leakage detection. While in pipeline leakage detection, fiber optic cables are installed permanently at the outside or within the protective sheathing of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…More extreme examples can be found in natural thermal ponds or pools with hot springs with up to 800 L min −1 discharge rates (Haselwimmer, Prakash, & Holdmann, ). Intense warm water discharge might also be of anthropogenic origin such as sewage leakage from under water pipes (Apperl, Pressl, & Schulz, ).…”
Section: Methodsmentioning
confidence: 99%
“…More extreme examples can be found in natural thermal ponds or pools with hot springs with up to 800 L min −1 discharge rates (Haselwimmer, Prakash, & Holdmann, ). Intense warm water discharge might also be of anthropogenic origin such as sewage leakage from under water pipes (Apperl, Pressl, & Schulz, ).…”
Section: Methodsmentioning
confidence: 99%
“…The outcome of the analysis revealed that the sensor is reliable in measuring the temperature and humidity data in harsh environments. Optical-based temperature sensors were experimented in sewers for various performance monitoring such as hydraulic performance, leakage monitoring [166], etc. Optical temperature sensor for hydraulics performance in sewer was experimented with backscatter light spectrum with less failure rate [167].…”
Section: Fiber Optic Temperature Sensorsmentioning
confidence: 99%
“…In the study, MPU6050 vibration sensor was used instead of the acoustic sensor because acoustic leak detection is only suitable for a metal pipeline. Their research motivation is to explore the effectiveness of using a vibration sensor since most of the existing research and study is using pressure sensor [13][14][15][16][17][18][19][20][21]. The water pipeline testbed is using ABS pipe approximately 10 meters length and a 1-inch diameter.…”
Section: External Systems 211 Sensor Basedmentioning
confidence: 99%
“…Distributed Temperature Sensing (DTS) technology is one of the commonly used methods to detect pipeline leakage. Preliminary works in DTS to localize the leakages in sewage pressure pipes were undertaken by [13]. The researchers utilize the DTS technology to measure the temperature along the fibre optic (FO) cable.…”
Section: Non-sensor Basedmentioning
confidence: 99%